A Rare t(3;15;17) in a Patient with Acute Promyelocytic Leukemia: Case Report and Review of the Literature - Linda Shi; Chu En Chen; Tahmeena Ahmed; Jacob Rocha; Pons Materum; Sashank Cherukuri; Leah Gallagher; Paula Fernicola; Roxana Ponce; Htien Lee; Christina Giordano; Gabriela Evans; et al. (Diagnostics)
We present a 48-year-old female with a past medical history of endometrioid adenocarcinoma who presented with symptoms of spontaneous gum bleeding, post-coital bleeding, and upper extremities–lower extremities-abdomen ecchymosis. Initial laboratory findings were significant for cytopenia and disseminated intravascular coagulation (DIC). Due to a suspected case of acute promyelocytic leukemia (APL), conventional karyotyping and fluorescence in situ hybridization (FISH) were performed. FISH analysis confirmed an unusual chromosome rearrangement that affected chromosomes 3, 15, and 17. This t(3;15;17)(q29;q24;q21) was characterized by the presence of PML::RARA fusion on the derivative chromosome 15. Treatment at the hospital with standard APL therapy of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) was complicated by the development of differentiation syndrome, which necessitated the temporary stoppage of ATO. However, complete remission was achieved despite complications after starting consolidation treatment.